EDUCATIONAL, SCIENTIFIC AND SOCIAL ACTIVITY OF E. O. SHAHAZIZ IN NAKHICHEVAN-ON-DON - N. A. Kazarova (Гуманитарные и юридические исследования)
The article studies the Nakhichevan period of educational, scientific and socio-political activity of the Armenian scholar Y.Shahaziz. He had been teaching in numerous educational institutions of the city for forty years. He was a member of different charitable organizations, ostensible member of the City Council and the organizer of the first city museum. It was in Nakhichevan, where he wrote a number of important scientific works on the history and ethnography of the Don Armenians.